ANALISIS STRATEGI PEMBANGUNAN EKONOMI PERTANIAN YANG BERKELANJUTAN DI WILAYAH PESISIR (Analysis of Sustainable Agricultural Economic Development Strategies in Coastal Areas) - Nur Inda Sari; Ikram Mubarak Djodding (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2024)
The purpose of this study is to support the development of agricultural economy in Jeneponto district, especially in coastal areas. The study participants involved farmers of different age groups, crop types, and levels of experience in the agricultural sector. The selection of participants was carried out deliberately to obtain a diversity of perspectives. Data will be collected through in-depth interviews. Thematic analysis will provide an in-depth understanding of farmers' perceptions, experiences, and views on the identified problems. The results of the thematic analysis will form the basis of the evaluation. Conclusions drawn from qualitative findings, and policy recommendations that are contextual and relevant to the daily reality of farmers in Jeneponto Regency will be formulated. The results of the study show that the majority of coastal residents in Jeneponto district in adopting sustainable agriculture are still very lacking and still very limited due to lack of access to agriculture and the majority of coastal people work as fishermen, 67% of respondents reported that they experienced an increase in agricultural income after they started cultivation activities by demonstrating the results of learning sustainable agricultural economics, especially in coastal areas. with an average increase of 20% in the following year.Keywords: Agricultural Economy, Coastal Areas, Development.